A Software Defined Wireless Networking Approach for Managing Handoff in IEEE 802.11 Networks. (21st November 2018) - Filho, José Quaresma; Cunha, Nailson; Lima, Robertson; Anjos, Eudisley; Matos, Fernando
Abstract : In Wireless Local Area Networks (WLAN) with more than one access point (AP), the handoff process plays a crucial role to guarantee the user service continuity. Usually initiated by the client's equipment, it occurs smoothly on the order of seconds. However, despite being functional and well-established, this process can be inadequate in scenarios where users are executing multimedia applications, such as real-time video streaming or VoIP. For these applications, those few seconds may cause loss of packets, resulting in loss of essential information. Because of that, this study proposes a Software Defined Wireless Networking (SDWN) approach, in which a controller decides when to initiate the handoff process and chooses the AP the client's device must connect. This approach was implemented in a testbed scenario and the results have shown its efficiency by decreasing the handoff delay and providing more stability to the process.